Pre-Service Teacher’s View towards 2013 Curriculum and School-based Curriculum - Anna Riana Suryanti Tambunan; Willem Saragih; Puan Suri Mira Annisa; Tiarnita M. S Siregar; Bahagia Saragih (English Department - University of Sultan Ageng Tirtayasa, 2019)
This study aims to discuss the views of pre-service teachers on the 2013 curriculum and KTSP. The implementation of the 2013 curriculum is very different from the previous curriculum. There are still many obstacles that significantly affect learning outcomes, both in terms of the media used, the assessment of the 2013 curriculum which is more complicated than the previous curriculum then the methods used to convey the learning material that has not been effective or not even following the learning material to communicate. This study used a qualitative descriptive method for two pre-service teachers who had the best GPA. In this study, researchers found that the 2013 curriculum was a new curriculum that followed the current technological era and also under the demands of the students' needs. Teacher candidates do not only learn how to understand teaching materials, but also how to apply these teaching materials in the teaching and learning process. In this study, researchers found that prospective teacher students faced obstacles in their application, for example in terms of classroom management and teaching preparation.Keywords: Curriculum 2013; pre-service teachers; school-based curriculumÂ Â